Serum vitamin D level, sun-exposed area, dietary factors, and physical activity as predictors of invasive breast cancer risk among Sudanese women: A case-control study - Husain, Nazik Elmalaika; Suliman, Ahmed A.; Abdelrahman, Ismail; Bedri, Shahinaz A.; Musa, Rasha M.; Osman, Hind E.; Mustafa, Ayda H.; Gafer, Nahla; Farah, Ehab; Satir, Ali Abdel; Ahmed, Mohamed H.; Osman, Mugtaba; et al. (Journal of Family Medicine and Primary Care, 2019)
Background: The role of vitamin D in the development, progression, and prognosis of breast cancer, though widely studied worldwide, has been inconclusive. This study intended to assess the role of some factors (including serum vitamin D level, sun-exposed area, dietary factors, and physical activity) as predictors of the development of invasive breast cancer (IBC) among Sudanese women. Methods: A case-control study was conducted on 200 Sudanese women (100 with newly diagnosed IBC and 100 matched healthy females). Serum 25-hydroxyvitamin D was measured through a competitive electrochemiluminescence immunoassay. Matching analysis was adopted by R version 3.4.1 making use of the "MatchIt" package for calculating propensity scores to build a confounder-adjusted, multiple generalized, linear logistic regression model. Results: Participants' age ranged from 28 to 85 years with a mean [+/- standard deviation (SD)] of 48.10 (+/- 12.11) years. The mean (+/- SD) serum vitamin D level was 12.97 (+/- 8.60) and 13.79 (+/- 6.79) ng/mL in breast cancer and noncancer Sudanese women, respectively [P = 0.013; odds ratio (OR) 0.862; 95% confidence interval (CI) 0.766-0.969; beta = 0.149)]. Sun-exposed area (P = 0.038; OR 0.013; 95% CI 0.000-0.782; beta = 4.339) is significantly and negatively associated with breast cancer development. While moderate physical activity (P = 0.0008; OR 2625.430; 95% CI 26.647-258673.001; beta = 7.873) is significantly and positively associated with IBC risk. Occasional consumption of milk, dairy products, eggs, and fish reduces the risk of developing IBC by 78.1%, 75.0%, 78.4%, and 76.4%, respectively. Conclusion: The higher the plasma vitamin D level by one unit, the lower the risk of breast cancer by 13.84%. Sedentary lifestyle, reduced sun-exposed skin area, and low serum vitamin D levels can be considered as predictors of IBC. Encouraging moderate physical activity and consumption of certain foods may, in part, decrease the precipitating risks of breast cancer. More studies and research are needed to confirm these findings.
CRIS-Team WoS Importer:2021-10-18